2013
DOI: 10.1088/0004-637x/769/1/33
|View full text |Cite
|
Sign up to set email alerts
|

MOSTOBSERVATIONS OF σ Ori E: CHALLENGING THE CENTRIFUGAL BREAKOUT NARRATIVE

Abstract: We present results from three weeks' photometric monitoring of the magnetic helium-strong star σ Ori E using the MOST microsatellite. The star's light curve is dominated by twice-per-rotation eclipse-like dimmings arising when magnetospheric clouds transit across and occult the stellar disk. However, no evidence is found for any abrupt centrifugal breakout of plasma from the magnetosphere, either in the residual flux or in the depths of the light minima. Motivated by this finding we compare the observationally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 37 publications
5
55
1
Order By: Relevance
“…Although these magnetospheres are dynamic in nature, there are many indications that their volumeintegrated properties are quite stable, namely based on numerical simulations (ud-Doula et al 2013), on observational diagnostics (Howarth et al 2007;Townsend et al 2013), and on the lack of short term variability observed here. With this picture in mind, we therefore do not expect the intrinsic X-ray emissivity of the magnetosphere itself to change significantly in time, but rather its sky-projected structure to modulate with the rotational phase.…”
Section: Spectral Analysismentioning
confidence: 67%
“…Although these magnetospheres are dynamic in nature, there are many indications that their volumeintegrated properties are quite stable, namely based on numerical simulations (ud-Doula et al 2013), on observational diagnostics (Howarth et al 2007;Townsend et al 2013), and on the lack of short term variability observed here. With this picture in mind, we therefore do not expect the intrinsic X-ray emissivity of the magnetosphere itself to change significantly in time, but rather its sky-projected structure to modulate with the rotational phase.…”
Section: Spectral Analysismentioning
confidence: 67%
“…In particular, the magnetic Be star σ Ori E shows clear∼5% eclipses twice per rotation period; these eclipses have been attributed to clouds of plasma thatare trapped in the magnetosphere and most dense at the corotation radius (Townsend et al 2013). The phenomenon of a narrow flux dip in phase with, and superposed on, semisinusoidal modulation has also been observed in the X-ray light curve of the accreting white dwarf PQ Gem (Mason 1997;Evans et al 2006).…”
Section: Transits Of Magnetospheric Clouds?mentioning
confidence: 88%
“…σ Ori E is a rapidly rotating Be star. Ground-based and MOST light curves for σ Ori E show it to have two short-duration flux dips (widths about 0.2 in phase) superposed on a wave-shaped undulation with a period of 1.19 days (Townsend et al 2013). The light-curve shape is apparently stable over many years.…”
Section: Could Scattered/emitted Light From Circumstellar Gasmentioning
confidence: 94%